SOSIALISASI PEMANFAATAN MEDIA SOSIAL UNTUK KEMANDIRIAN EKONOMI PEMUDA DI KENDARI - Irma Wanti; Moch Ricky Ramadhan; La Taya; La Tarifu; Hasriani Amin; La Iba; Joko Joko; Wa Ode Nila Farlin; Rekha Adji Pratama (Jurnal Pengabdian NUSANTARA, 2023)
The world is no longer round, but has become flat with the arrival of the internet. The increasing number of internet users after the pandemic has contributed to making the world flatter. The development of surveillance technology facilitates the transfer of information in real time from a remote corner of Indonesia to America, which can also be accessed instantly by the wider community, if the information is conveyed via television or website on the internet network. This encourages the creation of new professions such as content creators who utilize various social media platforms to support economic independence, especially for youth through social media. Internet users in regions, such as Kendari, Southeast Sulawesi, have also increased since 2020. However, until now, in general, the livelihoods of the people of Kendari city are still in the agriculture, plantation, livestock, fisheries and industrial sectors. Thus, this activity aims to build a new paradigm from the youth in Kendari city towards new livelihood variants by utilizing social media. The results of the socialization activities carried out, firstly, awakened awareness for the youth of Kendari city about the use of social media that can support economic independence. Second, the content creator profession is developing in Kendari city